The Characteristics of Polyester Concrete with Local Sand of East Borneo as Filter - Dewi, Asti Lolita; Tanjung, Rifqi Aulia; Tajalla, Gusti Umindya Nur; Parmita, Ade Wahyu Yusariarta Putra (Indonesian Applied Physics Letters, 2024)
Concrete is a mixture of coarse aggregate and fine aggregate mixed with water and cement as a binder and filler. The disadvantages of traditional concrete are that high water absorption causes low chemical resistance, low modulus of elasticity, low impact strength and a long hardening time to reach its maximum properties, namely 28 days. The solution to these shortcomings that is being developed for construction material applications is by using polymers as polymer concrete. In this research, polyester resin and sand aggregate were used as basic materials. Polyester resin is a type of thermosetting polymer that is widely used in various applications such as automotive parts, composites and construction because of its suitable processing characteristics and affordable price. Meanwhile, the sand used is local Kalimantan sand, where from the XRF and XRD test results, local Kalimantan sand is included in the silica sand type. This research varies the weight fraction of polyester resin used to determine its effect on polymer concrete characteristics such as porosity, water absorption, compressive strength, and macro observations. Variations in the polymer weight fraction used were 20%, 25% and 30%. Compressive strength testing was carried out at the age of 7 days of concrete. The results of the porosity test show that the average porosity of all variations is ± 0.5%. Meanwhile, the average value of water absorption for all fractions is 0.2%. And the highest average value of compressive strength in the 30% polyester resin weight fraction was 66.9 MPa. So it can be concluded that all variations meet SNI standards to become concrete materials.